Staging of personnel management in current economic conditions - A.S. Ustilovska; S.O. Bezruk (Економіка, управління та адміністрування)
The article analyzes the following stages of personnel management: personnel planning, recruitment and selection, adaptation, development, evaluation and certification. The essence of the personnel planning stage is revealed by the use of such methods as expert method, normative method, balance method, mathematical-statistical method and extrapolation method. The stage of recruitment and selection. Recruitment is defined as a six-step process: determining the need for new employees; determining the requirements for the candidate; search and recruitment of candidates for a vacant position; collecting candidate information; evaluation of candidates for the vacant position; deciding how to fill the vacancy, and as a result of employment, familiarization with the position. With regard to the selection of personnel, a number of methods are proposed, which are divided into traditional and non-traditional, including: an interview, questionnaires, assessment centers, testing, resumes; unconventional methods, in turn, include: physiognomy, socionics, graphology, fingerprint studies, shock interviews, brainteaser interviews, which are grouped into a schematic representation. The adaptation of staff is conventionally divided into four stages. The first stage is assessing the level of readiness of the newcomer, the second stage is orientation, the third stage is direct adaptation, and the fourth stage is functioning. The authors emphasize that the stage of personnel development is built through the personal growth of employees and to the improvement of production efficiency. The stage of assessment and personnel certification. The staff assessment is presented as the analysis of the employee's performance at a given workplace over a period of time, checking compliance with the performance standards according to specified criteria. The results of the evaluation are important for identifying «areas of immediate development» as well as the guidance for the further management of staff achievement, when staff appraisal as a procedure for systematically formally assessing the level of work, qualities and personality of employees meet the requirements of work performed. Certification allows to obtain information for further management decisions on which the classification is formed, provided that all the stages of personnel management are consistent and complete.